Analisis Yuridis Hukuman Mati pada Pelaku Tindak Pidana Pembunuhan Berencana - Nahak, Artha Ulina; Laila, Khotbatul; Pakpahan, Hatarto; Sabrina, Nahdiya; Lailawati, Fadilla Dwi (University of Merdeka Malang, 2023)
Premeditated murder is a criminal offense regulated in Article 340 of the Criminal Code whose criminal sanctions are much more severe than other criminal acts because someone who commits the crime of premeditated murder can be sentenced to the most severe crime, namely the death penalty. This research aims to determine the judge's considerations in imposing a crime on the crime of premeditated murder as well as the juridical analysis of the decision. In this research the author uses a normative juridical research method where what is studied is a court decision that already has permanent legal force. In related research the author used techniques for collecting primary, secondary and tertiary materials which include laws, copies of the Lamongan District Court decision Number 160/Pid.B/2020/PN.Lmg, literacy materials such as books, journals, the internet and also a thesis related to the death penalty and premeditated murder. From the research conducted, the author obtained the results of the panel of judges' considerations in handing down the death penalty to the perpetrator of the crime of premeditated murder without paying attention to the elements of the criminal's influence on the perpetrator's future, as well as elements of planning that were not genuinely proven. The death penalty imposed on perpetrators of the crime of premeditated murder is basically contrary to human rights and sociologically, many death sentences have not been executed since 2016 because of the memoratorium issued by the Indonesian government.